2021
DOI: 10.1016/j.scitotenv.2021.146380
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the COVID-19 air pollution decrease in Spain: Now what?

Abstract: We offer an overview of the COVID-19 -driven air quality changes across 11 metropolises in Spain with the focus on lessons learned on how continuing abating pollution. Traffic flow decreased by up to 80% during the lockdown and remained relatively low during the full relaxation (June and July). After the lockdown a significant shift from public transport to private vehicles (+21% in Barcelona) persisted due to the pervasive fear that using public transport might increase the risk of SARS-CoV-2 infection, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(65 citation statements)
references
References 47 publications
11
53
0
1
Order By: Relevance
“…Research focusing on South Asia critically investigated lockdown effects toward concentrations of air pollutants and found that a significant reduction of air quality index (AQI) was observed over most polluted ranked cities like Delhi, Dhaka, Kathmandu, Colombo due to the total shutdown [ [20] , [21] , [22] , [23] ]. Similar results have also been found at the all-countries level [ 24 ] such as Australia [ 25 ], UK [ 26 ], Italy [ 27 ], Spain [ 28 ], and Brazil [_Nakada_and_Urban_2020]. Above all, existing research mainly focuses on the air pollution change during the earlier stage of the COVID-19.…”
Section: Introductionsupporting
confidence: 68%
“…Research focusing on South Asia critically investigated lockdown effects toward concentrations of air pollutants and found that a significant reduction of air quality index (AQI) was observed over most polluted ranked cities like Delhi, Dhaka, Kathmandu, Colombo due to the total shutdown [ [20] , [21] , [22] , [23] ]. Similar results have also been found at the all-countries level [ 24 ] such as Australia [ 25 ], UK [ 26 ], Italy [ 27 ], Spain [ 28 ], and Brazil [_Nakada_and_Urban_2020]. Above all, existing research mainly focuses on the air pollution change during the earlier stage of the COVID-19.…”
Section: Introductionsupporting
confidence: 68%
“…On the other hand, an increase in O 3 levels (from +5 to +16%), most likely due to the low O 3 consumption by NO x oxidation, was accounted for after lockdown implementation. Similar reductions in pollutants levels (i.e., NO x , SO 2 , CO, O 3 , PM 10 , PM 2.5 , and BC) were reported in several cities of Spain during the lockdown period [5][6][7][8][9][10][11][12][13][14][15] Due to the increases in agricultural and domestic biomass burning during the lockdown, PM 2.5 and CO levels were also reduced less than expected, in agreement with results from other Spanish cities [5].…”
Section: Discussionsupporting
confidence: 84%
“…These measures have had good impacts on the air quality of cities around the world, alleviating air pollutants and improving air quality during the lockdown weeks as a consequence of reductions in road traffic, shipping, and industrial activities. The effect of the SARS-CoV-2 pandemic on the air quality of several cities of Spain confirmed these findings [5][6][7][8][9][10][11][12][13][14][15]. Similar positive impacts on air quality have been reported around several European cities [11,[16][17][18][19].…”
Section: Introductionsupporting
confidence: 72%
“…Levels of NO 2 for example fell by as much as 30%–50% in cities such as Delhi, Madrid and Wuhan, mainly because of road traffic decline (e.g. Querol et al, 2021 , Shi et al, 2021 ). Large areas of the world recorded similarly significant reductions in ambient PM 2.5 ( Bonardi et al, 2021 ), and CO 2 emissions from fossil fuel combustion fell by an estimate 2.6GtCO 2 in 2020, around 7% below that of 2019 ( Friedlingstein et al, 2020 , Le Quéré et al, 2021 ).…”
Section: Pandemic Preservation Potential In the Geological Recordmentioning
confidence: 99%